1989
DOI: 10.1093/bja/62.6.616
|View full text |Cite
|
Sign up to set email alerts
|

Use of Magnesium Sulphate in the Anaesthetic Management of Phaeochromocytoma: A Review of 17 Anaesthetics

Abstract: Seventeen anaesthetics are described in 16 patients with phaeochromocytoma in whom magnesium sulphate (MgSO4) was the principal anti-adrenergic agent used. In 15 of the 17 anaesthetics, MgSO4 produced satisfactory control of cardiovascular changes at induction and tracheal intubation, but in four of these additional sodium nitroprusside was required to control the arterial pressure during handling of the tumour. In one pregnant patient undergoing Caesarean section, MgSO4 was ineffective in controlling cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(71 citation statements)
references
References 0 publications
0
68
0
3
Order By: Relevance
“…These results show that intrathecally administered magnesium sulphate has little effect on electrolyte homeostasis. The increasing interest in magnesium as a physiological N-methyl-D-aspartate antagonist and its role in a variety of clinically important disorders characterised by intracellular calcium excess and magnesium deficiency [1][2][3][4][5] has prompted us to investigate the use of intrathecal magnesium sulphate in an experimental animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that intrathecally administered magnesium sulphate has little effect on electrolyte homeostasis. The increasing interest in magnesium as a physiological N-methyl-D-aspartate antagonist and its role in a variety of clinically important disorders characterised by intracellular calcium excess and magnesium deficiency [1][2][3][4][5] has prompted us to investigate the use of intrathecal magnesium sulphate in an experimental animal model.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that intrathecally administered magnesium sulphate has little effect on electrolyte homeostasis. The increasing interest in magnesium as a physiological N-methyl-D-aspartate antagonist and its role in a variety of clinically important disorders characterised by intracellular calcium excess and magnesium deficiency [1][2][3][4][5] has prompted us to investigate the use of intrathecal magnesium sulphate in an experimental animal model.We have previously shown that when injected intrathecally in a rat model, magnesium sulphate, in a concentration iso-osmolar with rat plasma, will produce a state of segmental spinal anaesthesia which is both completely reversible and free of neurotoxic side-effects [6,7]. However, the same volume and concentration which resulted in spinal anaesthesia, when injected intravenously, did not produce general anaesthesia sufficient for a laparotomy procedure to be carried out painlessly.…”
mentioning
confidence: 99%
“…The subsequent sudden intraoperative withdrawal of vasopressors following pheochromocytoma resection was believed to cause abrupt relaxation of the vascular bed, in turn resulting in hypotension and shock unless the reduced blood volume was restored (13)(14)(15). This led to the assumption that optimal preoperative care had to include preoperative vasodilation of the previously constricted vascular compartment by a vasodilating drug along with restoring blood volume by major fluid infusion (5,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…This improved prognosis is currently attributed to the widespread preoperative administration of vasodilating drugs and large fluid volumes, even in patients with normal or borderline elevation of catecholamine levels (5,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Nevertheless, none of these practices are evidence based, and to our opinion, a critical review of the available literature does not support this dogma.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Magnesium sulfate has been advocated because it inhibits the release of catecholamines from the adrenal medulla and adrenergic nerve endings, has direct vasodilatory effects and antiarrhythmic properties. 6,7 This patient was given a loading dose of 2 g on the morning of surgery and started on an infusion of 1 g·hr -1 , which was subsequently reduced on induction to 0.5 g·hr -1 and stopped intraoperatively after tumour removal.…”
Section: Discussionmentioning
confidence: 99%